The Women Poet: Exploring the Existence of Women and Feminist Values from the Song of Songs 3:1-5 - Pattiserlihun, Selvone Christin (Lembaga Penelitian dan Pengabdian pada Masyarakat Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2022)
Aren't humans created equally? in every situation, they are equal whatever the situation. Humans are social creatures who always depend on groups and cannot live alone to the fullest. Biologically, humans are classified based on sex in two forms, namely male (male) and female (female). Both men and women, humans still have the same awareness to express their existence in society. However, the awareness to accept existence (existence) is based on several conditions. The Bible is a place to describe the existence of women in society in terms of religion (Christianity). Women have always been objects and do not have the same existence as men, which was once based on public awareness (which was very patriarchal). One of the love poems, the Song of Solomon, records the existence of women and describes it clearly that women had a unique existence in society at the time of the writing of the Bible even before Jesus. This paper aims to explain the existence of women in Kidung Agung using a feminist literary criticism approach as a writer. The author would like to emphasize that the poem “Dream of the Bride” in Song of Solomon 3:1-5 was written by a woman. In the end, this paper will provide moral values ​​for women today.